EDUCAÇÃO AMBIENTAL CONTINUADA EM GESTÃO EMPRESARIAL: UM ESTUDO DE CASO EM UMA COMPANHIA SIDERÚRGICA - Silva, Viviane Maciel da (2007)
Faced with the urgent necessity of changing attitude and behaviors, the organizations have been assimilating and incorporating environmental issues in their objectives and aims. It is in this context so as the company can be adapting itself and providing the society a better quality of life as well, the Environmental Education is considered to be one of the means in which the individual is able to build social values, knowledge, skills and attitudes towards the environmental responsibility. So, the current research, through a field search has how beginning analyze opinions and suggestions of the employees from a steel metallurgy company situated in Grande Vitória. It sought to study the contribution of an Environmental Education Program to overcome old patterns existing concerning the environment; to ascertain the level of importance of the environmental administration of the company, since the success of the implementation of the environmental administration in an enterprise has a basic condition that is the commitment of all the contributors, including the main direction. To investigate still, if there was any change in the worker s behavior after the implementation of the program, so as being aware of the environmental issue they can contribute for the formation of a pro-active and environmentally responsible company.